An Investigation into the effectiveness of Management Accounting Practices in Manufacturing Companies based in Duhok City: UB Holding Group Companies as a Case Study - Ismail, Basheer Yousif; Hassan, Zeravan Fadhil (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research paper is to explore the role of management accounting tools as an important provider of useful information to internal users (managers) in order to make rational decisions. The study sample is UB Holding Group manufacturing company operating in Duhok City. In this regard, a questionnaire-based method has been used for collecting data from research participants, then processed via Statistical Package for the Social Sciences (SPSS). The research study concluded that management accounting techniques do not play significant role in the process of decision making of company study sample. As well as, company does not use neither actual costing system nor standards accounting system for controlling costs centres. Additionally, other managerial accounting tools such as break-even point, planning budgets were not being applied in the process of decision making.